(untitled) (The International Research Journal of Management Science, 2025)
Purpose: The purpose of this study is to examine the influence of financial education programs on students’ financial well-being with the serial mediation effects of social media influence and financial knowledge. Methods/Design: A cross-sectional survey was used with 416 undergraduate and graduate students from public and private colleges in Sudurpashim Province of Nepal. Data were analyzed using Structural Equation Modeling (SEM) with bootstrap procedures in SmartPLS 3.0. This approach was used to test the hypotheses concerning to the serial mediation effect of social media influence and financial knowledge. Findings: Financial education programs significantly enhance financial well-being primarily through an indirect serial pathway. The direct effect of financial education on students ’well-being was non-significant. The impact of financial education on students’ financial well-being does not occur directly but is fully mediated by a digital learning pathway involving social media and financial knowledge. Implications/Limitations: Universities should design comprehensive programs that highlight the crucial role of financial education programs in shaping university students’ financial well-being. Policymakers and financial service providers should use social media as a key channel for financial education. The study’s cross-sectional design and its geographic focus on one province in Nepal may limit the generalizability. Originality: This study provides a unique dimension of understanding whether financial education improves financial well-being by increasing financial knowledge, and whether it reduces exposure to social media influence, forming a sequential mediating pathway remains unexamined.